Sm with carbon-loaded TiO2(F) and transition metal particles added 1.7 Mg 98.3 Hydrogen storage alloy composite and method for producing the same
Patent Information
- Application Number
- CN202611121383.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-27
AI Technical Summary
然而,单一的合金化或添加剂掺杂策略仍存在局限性
1、本发明由Sm1.7Mg98.3合金粉末与碳负载的TiO2(F)与过渡金属颗粒通过氢化燃烧结合高能球磨法制备而成,其中过渡金属主要为Ni和Co;复合材料在制备以及吸放氢过程中逐渐生成多价的Ti(Ti4+、Ti3+、Ti2+、Ti0),能够周期性的转移电子,大幅度削弱Mg-H和H-H键能;原位生成的Sm3H7相和纳米晶MgO提供氢通道,降低氢扩散势垒,碳材料起到抑制镁颗粒过度生长的作用;Ni、Co等过渡金属在吸放氢循环中发挥氢泵等独特功效,最终构造多元素协同催化体系,既能有效削弱Mg-H和H-H键,提高材料的吸放氢动力学性能,又能显著促进H扩散,维持镁基材料的高容量;
Smart Images

Figure CN122979730A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid-state hydrogen storage materials, and relates to a Sm... 1.7 Mg 98.3 Hydrogen storage alloy composite materials and their preparation methods. Background Technology
[0002] Hydrogen is an ideal clean energy carrier. To store hydrogen more safely and efficiently, researchers have developed various solid-state hydrogen storage materials based on the principles of physical adsorption and chemical absorption. Magnesium hydride (MgH2) has a high theoretical hydrogen storage capacity (7.6 wt.%), low cost, and wide availability, making it a solid-state hydrogen storage material with great development potential. However, the thermodynamic stability and sluggish kinetics of MgH2 hinder its application in many scenarios. Lowering the energy barrier of hydrogen absorption and desorption processes in MgH2 and increasing the reaction rate are currently the main research directions for magnesium-based hydrogen storage.
[0003] Alloying is an effective way to improve the kinetic and thermodynamic properties of magnesium-based materials. By introducing other metallic elements to form stable intermetallic compounds or solid solutions with magnesium, the fundamental properties of the material can be controlled at the electronic structure level. For example, magnesium can be alloyed with rare earth elements (REs). Magnesium and REs (Sm, Ce, Y, Gd, etc.) can form REMg2 and RE5Mg. 41 RE2Mg 17 The binary hydrogen storage phase then generates MgH2 and REH in situ after hydrogenation. x REH x Many of these materials exhibit high stability and can serve as catalysts to accelerate hydrogen absorption and desorption. Doping the system with catalytically active substances is another effective strategy to improve the kinetic performance of magnesium-based materials. Ti-based compounds (TiO2, TiF3, etc.) can generate polyvalent Ti (TiO2, TiF3, etc.) in varying amounts during the hydrogen absorption and desorption process of magnesium-based materials. 2+ Ti 3+ (etc.), a stepwise transfer of electrons promotes interfacial reactions. Furthermore, Ti sites weaken Mg-H and HH bonds, promoting MgH2 decomposition by extending bond lengths. However, single alloying or additive doping strategies still have limitations. On the one hand, REH x The intrinsic catalytic efficiency of Ti is limited, resulting in insufficient improvement on the kinetic properties of magnesium-based materials. On the other hand, Ti-based compounds themselves lack physical barriers to magnesium particle growth, failing to inhibit material aggregation during high-temperature cycling.
[0004] Based on this, the present invention is proposed. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention aims to provide a Sm-based composite material with added carbon-supported TiO2(F) and transition metal particles. 1.7 Mg 98.3 Hydrogen storage alloy composite material and its preparation method, with chemical composition Sm 1.7 Mg 98.3 +10 wt.% TiO2(F) / M@C, where M is Co or Ni; the additive is obtained through a combination of hydrothermal synthesis and carbothermal reduction, and then subjected to a hydrogenation combustion-high-energy ball milling process with Sm 1.7 Mg 98.3 The alloy is used to prepare a hydrogen storage composite material. This material generates multivalent active sites during hydrogen absorption and desorption, which can effectively promote the dissociation of Mg-H and HH bonds. The in-situ generated Mg2Ni / Mg2NiH4 and Mg2Co / Mg2CoH5 act as "hydrogen pumps" to provide a fast hydrogen atom transfer channel, reduce the activation energy, and work synergistically with Ti active sites to accelerate hydrogen absorption and desorption. At the same time, the carbon layer inhibits the excessive growth and clustering of magnesium particles, avoiding capacity decay caused by high temperature.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A Sm-based composite material with added carbon-supported TiO2(F) and transition metal particles 1.7 Mg 98.3 Hydrogen storage alloy composite material with the general chemical formula Sm 1.7 Mg 98.3 +10 wt.%TiO2(F) / M@C, where M is Co or Ni.
[0007] This invention also provides a Sm-based composite material with added carbon-supported TiO2(F) and transition metal particles. 1.7 Mg 98.3 The preparation method of hydrogen storage alloy composite material shall be carried out in the following order: S1. Preparation of TiOF2 S11. Add tetrabutyl titanate and acetic acid to a beaker, and slowly add hydrofluoric acid dropwise into the system under magnetic stirring. Continue stirring at room temperature for 20-40 min to obtain the precursor solution. S12. The precursor solution was transferred to the PPL liner and subjected to hydrothermal treatment. The precipitate was washed with deionized water and anhydrous ethanol respectively. The precipitate was washed three times by centrifugation at 6000 rpm for 5 min each time. After freeze-drying in a freeze dryer for 3 days, TiOF2 was obtained. S2, Preparation of TiO2(F) / M@C S21. Disperse TiOF2 and metal salt in deionized water and stir thoroughly to dissolve. Add 3 g of polyvinyl alcohol to the solution, heat slowly in a water bath to 96 °C and stir continuously, interspersed with ultrasonic treatment to remove air bubbles in the colloid. After the polyvinyl alcohol is completely melted, place the sample in a low temperature freezer and freeze and thaw four times to obtain the precursor gel. S22. The precursor gel was placed in a tube furnace and heat-treated under an argon atmosphere to obtain TiO2(F) / M@C; S3, Preparation of Sm 1.7 Mg 98.3 +10 wt.% TiO2(F) / M@C hydrogen storage alloy composite material S31. Under an argon atmosphere, Sm 1.7 Mg 98.3 The alloy powder was mixed with 10 wt.% TiO2(F) / M@C powder and placed in a sample tube for pre-hydrogenation and hydrogenation to obtain a black powder; S32. Under an argon atmosphere, the black powder was placed in a stainless steel ball mill jar and ball-milled to obtain Sm. 1.7 Mg 98.3 +10wt.%TiO2(F) / M@C hydrogen storage alloy composite material.
[0008] As a limitation of the preparation method of the present invention, in step S11, the volume ratio between the tetrabutyl titanate, acetic acid, and hydrofluoric acid is 15:(10-40):5.
[0009] As another limitation of the preparation method of the present invention, in step S12, the temperature of the hydrothermal treatment is 180-200 ℃ and the time is 10-15 h.
[0010] As a third limitation of the preparation method of the present invention, in step S21, the metal salt is Ni(NO3)2·6H2O or Co(NO3)2·6H2O.
[0011] As a fourth limitation of the preparation method of the present invention, in step S21, the molar ratio of TiOF2 to metal salt is 1:(2.5-5.5).
[0012] In this invention, the type and amount of nitrate are crucial, affecting the loading, dispersion state, and synergistic catalytic effect of transition metal nanoparticles in the TiO2(F) / M@C composite additive with TiO2(F). When the molar ratio of TiOF2 to Ni(NO3)2·6H2O or Co(NO3)2·6H2O is controlled within the range of 1:(2.5-5.5), the transition metal ions are uniformly distributed in the gel precursor. After carbothermic reduction, uniform and well-dispersed metal nanoparticles can be generated, forming a heterogeneous interface with TiO2(F) in close contact. This fully leverages the synergistic catalytic effect of both in the hydrogen adsorption and desorption process and accelerates the hydrogen adsorption and desorption kinetics. When the molar ratio is below 1:2.5, the transition metal loading is insufficient, the number of catalytic active sites is limited, and it is difficult to form an effective synergistic effect with TiO2(F), resulting in limited improvement on the hydrogen storage performance of magnesium-based alloys. When the molar ratio is above 1:5.5, the transition metal loading is too high, and nanoparticles are prone to agglomeration and growth, leading to a decrease in the active specific surface area, which weakens the overall catalytic efficiency of the composite additive. The metallic Ni and Co generated by Ni(NO3)2·6H2O and Co(NO3)2·6H2O during carbothermic reduction can react with the Mg matrix during hydrogenation combustion-high-energy ball milling to form Mg2Ni / Mg2NiH4 and Mg2Co / Mg2CoH5 hydrogen pumps, reducing the activation energy for hydrogen decomposition and formation, and providing a rapid channel for hydrogen atoms to enter and exit the material matrix. Based on this, by selecting different types of nitrates, the catalytic characteristics of the composite additive can be directionally controlled according to actual application requirements.
[0013] As a fifth limitation of the preparation method of the present invention, in step S22, during the heat treatment, the temperature is first increased from room temperature to 230°C at a heating rate of 5°C / min and held for 30 min, and then increased from 230°C to 500°C at a heating rate of 10°C / min and held for 2 h.
[0014] As a sixth limitation of the preparation method of the present invention, in step S31, the temperature of the pre-hydrogenation is 425-550℃, the hydrogen pressure is 0.07-0.2 MPa, and the time is 1-4 h; the hydrogenation is first carried out once at 400℃ and 4.0 MPa for 12 h, and then hydrogenated at 300℃ and 4.0 MPa for 12 h, and the hydrogenation step at 300℃ is repeated twice.
[0015] In this invention, the pre-hydrogenation process is crucial and affects Sm 1.7 Mg 98.3 The initial activation state of the alloy and its subsequent hydrogenation decomposition efficiency. Pre-hydrogenation treatment of the mixture at 425-550 °C and 0.07-0.2 MPa hydrogen pressure for 1-4 h can improve the efficiency of Sm... 1.7Mg 98.3 The surface oxide layer of the alloy is broken down, forming a fresh active surface, which significantly reduces the energy barrier of the subsequent hydrogenation reaction, ensuring that the alloy can be completely hydrogenated and thus improving the hydrogen storage capacity of the composite material. If the pre-hydrogenation step is omitted, the oxide film on the alloy surface will hinder the diffusion and penetration of hydrogen molecules into the material interior, resulting in insufficient hydrogenation reaction and affecting the hydrogen storage capacity of the composite material. If the pre-hydrogenation temperature is below 425 °C or the time is less than 1 h, it is difficult to completely break down the passivation layer on the alloy surface, resulting in limited improvement in alloy activity and continued suppression of subsequent hydrogenation efficiency. If the pre-hydrogenation temperature is too high or the time is too long, it may lead to unnecessary sintering or grain coarsening of the alloy, which is also detrimental to the subsequent hydrogenation reaction. The formal hydrogenation step is repeated three times, with the first hydrogenation temperature at 400 °C and the subsequent two hydrogenation temperatures reduced to 300 °C. The gradient cooling hydrogenation strategy is adopted primarily because: the high temperature of 400 °C helps break the hydrogenation barrier of the alloy, promoting rapid initial hydrogenation; the subsequent temperature reduction to 300 °C prevents particle growth and agglomeration caused by prolonged high-temperature holding, thus avoiding a decrease in hydrogen storage capacity. Furthermore, the relatively mild hydrogenation conditions in the gradient hydrogenation strategy help maintain the original morphology and structural integrity of the TiO2(F) / M@C additive, avoiding metal nanoparticle agglomeration caused by high temperatures; on the other hand, the uniform and slow hydrogenation process facilitates the uniform dispersion of additive particles in the MgH2 matrix, avoiding additive segregation caused by localized violent reactions.
[0016] As a seventh limitation of the preparation method of the present invention, the ball milling process is as follows: ZrO2 and materials with a ball-to-material ratio of (35-60):1 are placed in a ball mill and ball milled at 400-550 rpm for 9-12 cycles, one cycle being: ball milling for 15-25 min, with an interval of 15-25 min.
[0017] This invention prepares Sm by a combination of hydrogenation combustion and high-energy ball milling. 1.7 Mg 98.3 +10 wt.% TiO2(F) / M@C (M=Co, Ni) composite hydrogen storage material. During hydrogenation combustion, Sm... 1.7 Mg 98.3 The alloy transforms into the MgH2 phase and a small amount of the Sm3H7 phase. Simultaneously, the TiO2(F) in TiO2(F) / M@C is partially reduced under a hydrogen atmosphere, generating multivalent Ti active sites (Ti). 4+ Ti 3 + Ti 2+ Ti 0The transition metal M (Co or Ni) is uniformly dispersed in the MgH2 matrix as nanoparticles, partially transforming into Mg2Ni / Mg2NiH4 and Mg2Co / Mg2CoH5 hydrogen pumps. Subsequently, high-energy ball milling further reduces the size of the MgH2 matrix to the micrometer scale, shortens the hydrogen diffusion distance, and promotes the uniform dispersion of Sm3H7 and TiO2(F) / M@C, providing additional hydrogen diffusion paths and thus accelerating hydrogen adsorption and desorption kinetics.
[0018] In this invention, the introduction of the carbon layer has multiple functions. On the one hand, it acts as a physical barrier, effectively inhibiting the excessive growth and aggregation of Mg particles during the hydrogen absorption and desorption cycle, thus avoiding hydrogen storage capacity decay caused by high temperature. On the other hand, the carbon layer has good electrical conductivity, which can promote the transfer of electrons between TiO2(F) and transition metals, enhancing the synergistic catalytic effect of the two.
[0019] This invention introduces multivalent Ti active sites, transition metal nanoparticles, and a carbon layer through interface engineering to construct a TiO2(F)-M@C interface with multiple synergistic functions. In this interface, multivalent Ti(F) active sites, transition metal nanoparticles, and a carbon layer are introduced. 4+ Ti 3+ Ti 2+ Ti 0 The composite material effectively weakens Mg-H and HH bonds through a step-like electron transfer effect, lowering their dissociation energy barrier. Mg2Ni / Mg2NiH4 and Mg2Co / Mg2CoH5 hydrogen pumps provide a fast channel for hydrogen atom transfer, reducing the activation energy and synergistically accelerating hydrogen adsorption and desorption reactions with the Ti active sites. The carbon layer, while inhibiting Mg particle growth, stabilizes the active sites of Ti and transition metals, preventing their deactivation. The synergistic effect of these three elements promotes hydrogen diffusion and recombination, accelerating hydrogen adsorption and desorption kinetics, while also inhibiting the aggregation and deactivation of additive particles, ultimately achieving excellent cycle stability.
[0020] The above-mentioned technical solution of the present invention is a whole in which each step is closely related and mutually influential, and together they determine the morphological characteristics and performance of the product.
[0021] The above technical solution has the following advantages or beneficial effects: 1. This invention is based on Sm 1.7 Mg 98.3 Alloy powder, carbon-supported TiO2(F), and transition metal particles were prepared by hydrogenation combustion combined with high-energy ball milling. The main transition metals were Ni and Co. During the preparation and hydrogen absorption / desorption processes, multivalent Ti(Ti) particles were gradually generated in the composite material. 4+ Ti 3+ Ti 2+ Ti 0The system can periodically transfer electrons, significantly weakening the Mg-H and HH bond energies; the in-situ generated Sm3H7 phase and nanocrystalline MgO provide hydrogen channels, reducing the hydrogen diffusion barrier; carbon materials play a role in inhibiting the excessive growth of magnesium particles; transition metals such as Ni and Co play unique roles such as hydrogen pumps in the hydrogen absorption and desorption cycle, ultimately constructing a multi-element synergistic catalytic system that can effectively weaken the Mg-H and HH bonds, improve the hydrogen absorption and desorption kinetics of the material, and significantly promote H diffusion, maintaining the high capacity of magnesium-based materials. 2. The Sm prepared by this invention 1.7 Mg 98.3 The +10 wt.%TiO2(F) / M@C (M=Co, Ni) composite material absorbs hydrogen at low temperatures with an initial hydrogen release temperature of less than 240 ℃, and retains more than 98% of its capacity after 50 cycles at 325 ℃. 3. The preparation method of this invention is simple, the process is easy to control, and it is convenient for industrial application.
[0022] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. Attached Figure Description
[0023] Figure 1 The hydrogen absorption and desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 1 of the present invention are shown, wherein: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Figure 2 The hydrogen absorption and desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 2 of the present invention are shown, wherein: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Figure 3 The hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 3 of the present invention are shown, wherein: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Figure 4 The hydrogen absorption and desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 4 of the present invention are shown, wherein: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Figure 5 The hydrogen absorption and desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 5 of the present invention are shown, wherein: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Figure 6The hydrogen absorption and desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 6 of the present invention are shown, wherein: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Figure 7 The hydrogen absorption and desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 7 of the present invention are shown, wherein: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Figure 8 The hydrogen absorption and desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Comparative Example 1 of this invention are shown, wherein: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Figure 9 The hydrogen absorption and desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Comparative Example 2 of this invention are shown, where: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Figure 10 The hydrogen absorption and desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Comparative Example 3 of this invention are shown, where: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Figure 11 The hydrogen absorption and desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Comparative Example 4 of this invention are shown, where: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Figure 12 The hydrogen absorption and desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Comparative Example 5 of this invention are shown, where: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Figure 13 The figures show the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Comparative Example 6 of this invention, where: a is the hydrogen absorption curve at 200 °C, b is the hydrogen desorption curve at 300 °C, and c is the cycling curve at 325 °C. Detailed Implementation
[0024] The following embodiments are merely some, not all, of the embodiments of the present invention. Therefore, the detailed descriptions of the embodiments provided below are not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0025] In this invention, unless otherwise specified, all equipment and raw materials are commercially available or commonly used in the industry. The methods described in the following embodiments are conventional methods in the art, unless otherwise specified.
[0026] Example 1
[0027] This embodiment prepares a Sm 1.7 Mg 98.3 The preparation process and steps of the +10 wt.% TiO2(F) / Ni@C hydrogen storage alloy composite material are as follows: S1. Preparation of TiOF2 S11. Add 15 mL of tetrabutyl titanate and 30 mL of acetic acid to 100 mL of plastic beaker. Under magnetic stirring, slowly add 5 mL of hydrofluoric acid to the system. Continue stirring at room temperature for 30 min to obtain the precursor solution. S12. The precursor solution was transferred to a 100 mL PPL liner and hydrothermally treated at 200 °C for 12 h. The precipitate was washed with deionized water and anhydrous ethanol, respectively, and centrifuged at 6000 rpm for 5 min each time. After freeze-drying in a freeze dryer for 3 days, TiOF2 was obtained. S2, Preparation of TiO2(F) / Ni@C S21. Dissolve 0.33 g TiOF2 and 4 g Ni(NO3)2·6H2O in 8 mL of deionized water by stirring thoroughly. Add 3 g polyvinyl alcohol to the solution, heat slowly in a water bath to 96 °C while stirring continuously, and sonicate intermittently to remove air bubbles from the colloid. After the polyvinyl alcohol has completely melted, place the sample in a low-temperature freezer and freeze and thaw four times to obtain the precursor gel. S22. The precursor gel was placed in a tube furnace and heated from room temperature to 230 °C at a heating rate of 5 °C / min under an argon atmosphere, and held for 30 min. Then, the temperature was increased from 230 °C to 500 °C at a heating rate of 10 °C / min and held for 2 h to obtain TiO2(F) / Ni@C. S3, Preparation of Sm 1.7 Mg 98.3 +10 wt.% TiO2(F) / Ni@C hydrogen storage alloy composite material S31. Under an argon atmosphere, Sm 1.7 Mg 98.3 The alloy powder was mixed with 10 wt.% TiO2(F) / Ni@C powder and placed in a sample tube. First, it was pre-hydrogenated at 500 °C and 0.1 MPa for 2 h. Then, the temperature was controlled to 400 °C and hydrogenated at 4.0 MPa for 12 h. After that, the temperature was controlled to 300 °C and hydrogenated twice at 4 MPa for 12 h each time to obtain black powder. S32. Under an argon atmosphere, the black powder was placed in a stainless steel ball mill jar for ball milling. The ball milling process was as follows: ZrO2 balls with a ball-to-material ratio of 50:1 and the material were placed in a ball mill and ball milled at 450 rpm for 9 cycles. One cycle consisted of 20 minutes of ball milling followed by a 20-minute interval, yielding Sm. 1.7 Mg 98.3 +10 wt.% TiO2(F) / Ni@C hydrogen storage alloy composite material.
[0028] Example 2
[0029] This embodiment prepares a Sm 1.7 Mg 98.3 The preparation process and steps of the +10 wt.% TiO2(F) / Co@C hydrogen storage alloy composite material are as follows: S1. Preparation of TiOF2 S11. Add 15 mL of tetrabutyl titanate and 30 mL of acetic acid to 100 mL of plastic beaker. Under magnetic stirring, slowly add 5 mL of hydrofluoric acid to the system. Continue stirring at room temperature for 30 min to obtain the precursor solution. S12. The precursor solution was transferred to a 100 mL PPL liner and hydrothermally treated at 180 °C for 15 h. The precipitate was washed with deionized water and anhydrous ethanol, respectively, and centrifuged at 6000 rpm for 5 min each time. After freeze-drying in a freeze dryer for 3 days, TiOF2 was obtained. S2, Preparation of TiO2(F) / Co@C S21. Dissolve 0.33 g TiOF2 and 4 g Co(NO3)2·6H2O in 8 mL of deionized water by stirring thoroughly. Add 3 g polyvinyl alcohol to the solution, heat slowly in a water bath to 96 °C and stir continuously, interspersed with sonication to remove air bubbles in the colloid. After the polyvinyl alcohol has completely melted, place the sample in a low-temperature freezer and freeze and thaw four times to obtain the precursor gel. S22. The precursor gel was placed in a tube furnace and heated from room temperature to 230 ℃ at a heating rate of 5 ℃ / min under an argon atmosphere, and held for 30 min. Then, the temperature was increased from 230 ℃ to 500 ℃ at a heating rate of 10 ℃ / min and held for 2 h to obtain TiO2(F) / Co@C. S3, Preparation of Sm 1.7 Mg 98.3 +10 wt.% TiO2(F) / Co@C hydrogen storage alloy composite material S31. Under an argon atmosphere, Sm 1.7 Mg 98.3 The alloy powder was mixed with 10 wt.% TiO2(F) / Co@C powder and placed in a sample tube. First, it was pre-hydrogenated at 500 °C and 0.1 MPa for 2 h. Then, the temperature was controlled to 400 °C and hydrogenated at 4.0 MPa for 12 h. After that, the temperature was controlled to 300 °C and hydrogenated twice at 4 MPa for 12 h each time to obtain a black powder. S32. Under an argon atmosphere, the black powder was placed in a stainless steel ball mill jar for ball milling. The ball milling process was as follows: ZrO2 balls with a ball-to-material ratio of 35:1 and the material were placed in a ball mill and ball milled at 550 rpm for 10 cycles. One cycle consisted of 15 minutes of ball milling followed by a 15-minute interval, yielding Sm. 1.7 Mg 98.3 +10 wt.%TiO2(F) / Co@C hydrogen storage alloy composite material.
[0030] Examples 3-7
[0031] Examples 3-7 each prepared a hydrogen storage alloy composite material. The preparation process was similar to that of Example 1, except that the parameters in the preparation process were different, as shown in the table below:
[0032] Comparative Example To investigate the influence of different preparation processes on the performance of the product of this invention, the following comparative experiments were conducted. Different hydrogen storage alloys were prepared in the following comparative examples: Comparative Example 1 This comparative example prepared Sm without any additives. 1.7 Mg 98.3 The hydrogen storage alloy is prepared as follows: (1) Sm with a size of 300 μm 1.7 Mg 98.3The alloy powder was placed in a sample tube and first pre-hydrogenated at 500 °C and 0.1 MPa for 2 h. Then the temperature was controlled to 400 °C and hydrogenated at 4.0 MPa for 12 h. After that, the temperature was controlled to 300 °C and hydrogenated twice at 4 MPa for 12 h each time to obtain black powder. (2) Under an argon atmosphere, the black powder was placed in a stainless steel ball mill jar for ball milling. The ball milling process was as follows: ZrO2 balls with a ball-to-material ratio of 40:1 and the material were placed in a ball mill and ball milled at 400 rpm for 9 cycles. One cycle consisted of 20 min of ball milling followed by a 20 min interval to obtain Sm. 1.7 Mg 98.3 Hydrogen storage alloy sample.
[0033] Comparative Example 2 This comparative example prepares a Mg+10 wt.%TiO2(F) / Ni@C hydrogen storage material. The preparation process is similar to that of Example 1, except that the Sm in step S31 is removed. 1.7 Mg 98.3 Replace all with Mg.
[0034] Comparative Example 3 This comparative example prepares a Sm 1.7 Mg 98.3 +10 wt.%TiO2(F)@C hydrogen storage alloy, the preparation process is similar to that of Example 1, the only difference being that Ni(NO3)2·6H2O is not added in step S21.
[0035] Comparative Example 4 This comparative example prepares a Sm 1.7 Mg 98.3 +10 wt.% Ni@C hydrogen storage alloy, the preparation process is similar to that of Example 1, except that step S1 is not performed and TiOF2 is not added in step S21.
[0036] Comparative Example 5 This comparative example prepares a Sm 1.7 Mg 98.3 The +10 wt.%TiO2(F) / Ni@C hydrogen storage alloy was prepared in a similar manner to that in Example 1, except that the pre-hydrogenation operation was omitted in step S31.
[0037] Comparative Example 6 This comparative example prepares a Sm 1.7 Mg 98.3 The +10 wt.%TiO2(F) / Ni@C hydrogen storage alloy was prepared in a similar manner to that in Example 1, except that the temperature of the three formal hydrogenations in step S31 was 400 °C.
[0038] Performance testing The hydrogen storage alloy composite materials prepared in Examples 1-7 and Comparative Examples 1-6 were tested for hydrogen absorption performance at 200 °C and 3.0 MPa hydrogen pressure, and for hydrogen desorption performance at 300 °C and 0.0006 MPa hydrogen pressure. A 50-cycle hydrogen absorption / desorption performance test was also conducted at 325 °C, with a hydrogen pressure of 3.0 MPa during absorption and 0.0006 MPa during desorption. The specific test results are as follows: like Figure 1 Figure 1 shows the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 1 of this invention. Figure 2 shows the hydrogen absorption curve at 200 °C, figure 3 shows the hydrogen desorption curve at 300 °C, and figure 4 shows the cycling curve at 325 °C. As can be seen from the figures, at 200 °C, the hydrogen absorption capacity of the hydrogen storage alloy composite material is 6.129 wt.% within 3600 s; at 300 °C, the hydrogen desorption capacity is 5.559 wt.% within 3600 s, reaching 95% of the maximum hydrogen desorption capacity within 750 s; the initial hydrogen desorption temperature is 235 °C; after 50 cycles, the hydrogen absorption / desorption rate of the composite material does not slow down, and the capacity retention rates during hydrogen absorption and desorption are as high as 99.2% and 98.6%, respectively.
[0039] like Figure 2 Figure 1 shows the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 2 of this invention. Figure 2 shows the hydrogen absorption curve at 200 °C, figure 3 shows the hydrogen desorption curve at 300 °C, and figure 4 shows the cycling curve at 325 °C. As can be seen from the figures, the final hydrogen absorption capacity of the hydrogen storage alloy composite material at 200 °C is 5.742 wt.%; the initial hydrogen desorption temperature is 239 °C; the final hydrogen desorption capacity at 300 °C is 5.531 wt.%, reaching 95% of the maximum hydrogen desorption capacity within 800 s; subsequently, after 50 cycles of hydrogen absorption / desorption at 325 °C, the capacity retention rates for hydrogen absorption and desorption are 99.0% and 98.9%, respectively.
[0040] like Figure 3 Figure 1 shows the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 3 of this invention. Figure 2 shows the hydrogen absorption curve at 200 °C, figure 3 shows the hydrogen desorption curve at 300 °C, and figure 4 shows the cycling curve at 325 °C. As can be seen from the figures, the hydrogen storage alloy composite material absorbs 5.604 wt.% hydrogen at 200 °C within 3600 s; the initial hydrogen desorption temperature is 237 °C; the maximum hydrogen desorption at 300 °C is 5.411 wt.%; and after 50 cycles of hydrogen absorption / desorption at 325 °C, the capacity retention rates for hydrogen absorption and desorption are 99.2% and 98.5%, respectively.
[0041] like Figure 4Figure 1 shows the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 4 of this invention. Figure 2 shows the hydrogen absorption curve at 200 °C, figure 3 shows the hydrogen desorption curve at 300 °C, and figure 4 shows the cycling curve at 325 °C. As can be seen from the figures, the hydrogen storage alloy composite material absorbs 5.549 wt.% hydrogen within 3600 s at 200 °C; the initial hydrogen desorption temperature is 233 °C; the maximum hydrogen desorption at 300 °C is 5.473 wt.%; and after 50 cycles of hydrogen absorption / desorption at 325 °C, the capacity retention rates for hydrogen absorption and desorption are 99.3% and 98.7%, respectively.
[0042] like Figure 5 Figure 1 shows the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 5 of this invention. Figure 2 shows the hydrogen absorption curve at 200 °C, figure 3 shows the hydrogen desorption curve at 300 °C, and figure 4 shows the cycling curve at 325 °C. As can be seen from the figures, the hydrogen storage alloy composite material absorbs 5.911 wt.% hydrogen at 200 °C within 3600 s; the initial hydrogen desorption temperature is 236 °C; the maximum hydrogen desorption at 300 °C is 5.603 wt.%; and after 50 cycles of hydrogen absorption / desorption at 325 °C, the capacity retention rates for hydrogen absorption and desorption are 98.7% and 98.2%, respectively.
[0043] like Figure 6 Figure 1 shows the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 6 of this invention. Figure 2 shows the hydrogen absorption curve at 200 °C, figure 3 shows the hydrogen desorption curve at 300 °C, and figure 4 shows the cycling curve at 325 °C. As can be seen from the figures, the hydrogen storage alloy composite material absorbs 6.015 wt.% hydrogen within 3600 s at 200 °C; the initial hydrogen desorption temperature is 238 °C; the maximum hydrogen desorption at 300 °C is 5.592 wt.%; and after 50 cycles of hydrogen absorption / desorption at 325 °C, the capacity retention rates for hydrogen absorption and desorption are 99.1% and 98.8%, respectively.
[0044] like Figure 7 Figure 1 shows the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Example 7 of this invention. Figure 2 shows the hydrogen absorption curve at 200 °C, figure 3 shows the hydrogen desorption curve at 300 °C, and figure 4 shows the cycling curve at 325 °C. As can be seen from the figures, the hydrogen storage alloy composite material absorbs 5.709 wt.% hydrogen within 3600 s at 200 °C; the initial hydrogen desorption temperature is 235 °C; the maximum hydrogen desorption at 300 °C is 5.497 wt.%; and after 50 cycles of hydrogen absorption / desorption at 325 °C, the capacity retention rates for hydrogen absorption and desorption are 99.3% and 98.2%, respectively.
[0045] like Figure 8 Sm prepared as Comparative Example 1 of this invention 1.7 Mg 98.3 Hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy are shown, where: a) is the hydrogen absorption curve at 200 °C, b) is the hydrogen desorption curve at 300 °C, and c) is the cycling curve at 325 °C. The figures show that the alloy absorbs 5.012 wt.% hydrogen within 3600 s at 200 °C; the initial hydrogen desorption temperature is 295 °C; the maximum hydrogen desorption at 300 °C is 4.323 wt.%; and after 50 cycles at 325 °C, the capacity retention rates for hydrogen absorption and desorption are 93.1% and 81.3%, respectively. Pure Sm... 1.7 Mg 98.3 In the hydrogen storage alloy, the Sm3H7 generated during hydrogenation serves as the main catalytic phase, providing hydrogen diffusion channels and accelerating hydrogen diffusion. However, it has little effect on weakening Mg-H and HH bonds. Therefore, during hydrogen absorption, hydrogen molecules need to dissociate into hydrogen atoms before diffusing into the alloy matrix. Due to the lack of an efficient hydrogen dissociation catalyst, the dissociation rate of hydrogen molecules is limited, resulting in a slow hydrogen absorption rate. During hydrogen desorption, because the Mg-H bonds are not effectively weakened, the diffusion and recombination of hydrogen atoms and the desorption of hydrogen molecules need to overcome a higher energy barrier, resulting in a lower hydrogen desorption rate than in the embodiments of the present invention, while the initial hydrogen desorption temperature is also higher than in the embodiments of the present invention.
[0046] like Figure 9 Figure 1 shows the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage composite material prepared in Comparative Example 2 of this invention. Figure 2 shows the hydrogen absorption curve at 200 °C, figure 3 shows the hydrogen desorption curve at 300 °C, and figure 4 shows the cycling curve at 325 °C. As can be seen from the figures, the composite material absorbed 5.892 wt.% hydrogen within 3600 s at 200 °C; the initial hydrogen desorption temperature was 281 °C; the maximum hydrogen desorption at 300 °C was 4.821 wt.%; and after 50 cycles of hydrogen absorption / desorption at 325 °C, the capacity retention rates were 96.9% and 96.4%, respectively. When using Mg+10 wt.%TiO2(F) / Ni@C hydrogen storage material, the system lacks the additional hydrogen diffusion channels provided by the Sm3H7 catalytic phase, resulting in a relatively simple hydrogen diffusion path. Long-range diffusion of hydrogen atoms requires overcoming a higher energy barrier, leading to a lower hydrogen absorption / desorption rate compared to the embodiments of this invention. Furthermore, Sm3H7, as a stable rare earth hydride phase, can support and stabilize the MgH2 matrix during cycling. In contrast, the pure MgH2 system lacks this structural stabilization effect and is more prone to particle agglomeration during long-term cycling, resulting in lower cycling stability than in the embodiments of the present invention.
[0047] like Figure 10Figure 1 shows the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Comparative Example 3 of this invention. Figure 2 shows the hydrogen absorption curve at 200 °C, figure 3 shows the hydrogen desorption curve at 300 °C, and figure 4 shows the cycling curve at 325 °C. As can be seen from the figures, the composite material absorbed 6.034 wt.% hydrogen within 3600 s at 200 °C; the initial hydrogen desorption temperature was 257 °C; the maximum hydrogen desorption at 300 °C was 4.503 wt.%; and after 50 cycles of hydrogen absorption / desorption at 325 °C, the capacity retention rates for hydrogen absorption and desorption were 97.0% and 97.6%, respectively. (Sm...) 1.7 Mg 98.3 In the +10 wt.% TiO2(F)@C hydrogen storage alloy, the system lacks the synergistic catalysis of transition metal M (Co or Ni) nanoparticles. Transition metals Co and Ni possess excellent hydrogen molecule dissociation and recombination capabilities, acting as hydrogen pumps. Without these components, relying solely on the catalytic effect of TiO2(F)@C limits the dissociation and recombination rates of hydrogen molecules, significantly reducing the hydrogen absorption and desorption rates, and resulting in an initial hydrogen desorption temperature slightly higher than in the embodiments of this invention. Furthermore, the absence of Co and Ni weakens the structural stability of the composite additive, making TiO2(F) particles more prone to aggregation during long-term cycling, leading to a slightly lower cycling stability compared to the embodiments of this invention.
[0048] like Figure 11 Figure 1 shows the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Comparative Example 4 of this invention. Figure 2 shows the hydrogen absorption curve at 200 °C, figure 3 shows the hydrogen desorption curve at 300 °C, and figure 4 shows the cycling curve at 325 °C. As can be seen from the figures, the composite material absorbed 5.619 wt.% hydrogen within 3600 s at 200 °C; the initial hydrogen desorption temperature was 262 °C; the maximum hydrogen desorption at 300 °C was 4.691 wt.%; and after 50 cycles of hydrogen absorption / desorption at 325 °C, the capacity retention rates for hydrogen absorption and desorption were 98.9% and 98.7%, respectively. (Sm...) 1.7 Mg 98.3 In the +10 wt.% Ni@C hydrogen storage alloy, the system lacks TiO2(F) component, thus losing the weakening effect of multivalent Ti active sites on Mg-H bonds. While relying solely on the catalytic effect of Ni nanoparticles exhibits a good hydrogen pumping effect, its direct weakening effect on Mg-H bonds is limited, resulting in a smaller reduction in the hydrogen desorption reaction energy barrier. Therefore, its initial hydrogen desorption temperature is significantly higher than that of the embodiments of the present invention, and its hydrogen desorption rate and amount are also lower than those of the embodiments of the present invention.
[0049] like Figure 12Figure 1 shows the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Comparative Example 5 of this invention. Figure 2 shows the hydrogen absorption curve at 200 °C, figure 3 shows the hydrogen desorption curve at 300 °C, and figure 4 shows the cycling curve at 325 °C. As can be seen from the figures, the composite material absorbed 5.403 wt.% hydrogen within 3600 s at 200 °C; the initial hydrogen desorption temperature was 257 °C; the maximum hydrogen desorption at 300 °C was 4.919 wt.%; and after 50 cycles of hydrogen absorption / desorption at 325 °C, the capacity retention rates were 95.7% and 89.2%, respectively. After canceling the pre-hydrogenation operation, the dense oxide layer on the alloy surface was not effectively broken down, resulting in a lack of fresh active surfaces within the system. The oxide film on the alloy surface hindered the diffusion and penetration of hydrogen molecules into the material, leading to incomplete subsequent hydrogenation reactions. Therefore, its hydrogen absorption and desorption capacities are lower than those of the embodiments of the present invention. Furthermore, the absence of a pre-hydrogenation step prevents the alloy from being fully activated, hindering the synergistic catalytic effect of multivalent Ti sites and Ni nanoparticles. The initial hydrogen desorption temperature is slightly higher than that of the embodiments of the present invention. Regarding cycle stability, due to insufficient initial hydrogenation, unhydrogenated phases exist within the material. These phases undergo repeated hydrogenation and dehydrogenation volume changes during subsequent cycles, exacerbating microstructural instability and particle agglomeration. Consequently, the hydrogen desorption capacity retention rate after 50 cycles is significantly lower than that of the embodiments of the present invention.
[0050] like Figure 13 Figure 1 shows the hydrogen absorption / desorption curves and cycling curves of the hydrogen storage alloy composite material prepared in Comparative Example 6 of this invention. Figure 2 shows the hydrogen absorption curve at 200 °C, figure 3 shows the hydrogen desorption curve at 300 °C, and figure 4 shows the cycling curve at 325 °C. As can be seen from the figures, the composite material absorbed 5.621 wt.% hydrogen within 3600 s at 200 °C; the initial hydrogen desorption temperature was 246 °C; the maximum hydrogen desorption at 300 °C was 4.722 wt.%; and after 50 cycles of hydrogen absorption / desorption at 325 °C, the capacity retention rates were 97.8% and 96.7%, respectively. Without the gradient cooling hydrogenation strategy, the three hydrogenation temperatures were all 400 °C. Excessive heat treatment at high temperatures led to excessive growth and agglomeration of magnesium particles, resulting in coarsening and uneven distribution of the Sm3H7 phase and TiO2(F) / Ni@C particles. Consequently, the hydrogen absorption and desorption kinetics of the material were lower than those of the embodiments of the present invention. Regarding cycle stability, although the carbon layer provided some physical barrier, the coarsened particles were more difficult to maintain structural stability in subsequent cycles. Therefore, the hydrogen desorption capacity retention rate after 50 cycles was slightly lower than that of the embodiments of the present invention.
[0051] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A SmS2 substrate with added carbon-supported TiO2(F) and transition metal particles 1.7 Mg 98.3 Hydrogen storage alloy composite material, characterized in that, The general chemical formula is Sm 1.7 Mg 98.3 +10 wt.%TiO2(F) / M@C, where M is Co or Ni.
2. The SmS ... 1.7 Mg 98.3 A method for preparing hydrogen storage alloy composite materials, characterized in that, Follow these steps in sequence: S1. Preparation of TiOF2 S11. Add tetrabutyl titanate and acetic acid to a beaker, and slowly add hydrofluoric acid dropwise into the system under magnetic stirring. Continue stirring at room temperature for 20-40 min to obtain the precursor solution. S12. The precursor solution was transferred to the PPL liner and subjected to hydrothermal treatment. The precipitate was washed with deionized water and anhydrous ethanol respectively. The precipitate was washed three times by centrifugation at 6000 rpm for 5 min each time. After freeze-drying in a freeze dryer for 3 days, TiOF2 was obtained. S2, Preparation of TiO2(F) / M@C S21. Disperse TiOF2 and metal salt in deionized water and stir thoroughly to dissolve. Add 3 g of polyvinyl alcohol to the solution, heat slowly in a water bath to 96 °C and stir continuously, interspersed with ultrasonic treatment to remove air bubbles in the colloid. After the polyvinyl alcohol is completely melted, place the sample in a low temperature freezer and freeze and thaw four times to obtain the precursor gel. S22. The precursor gel was placed in a tube furnace and heat-treated under an argon atmosphere to obtain TiO2(F) / M@C; S3, Preparation of Sm 1.7 Mg 98.3 +10 wt.% TiO2(F) / M@C hydrogen storage alloy composite material S31. Under an argon atmosphere, Sm 1.7 Mg 98.3 The alloy powder was mixed with 10 wt.% TiO2(F) / M@C powder and placed in a sample tube for pre-hydrogenation and hydrogenation to obtain a black powder; S32. Under an argon atmosphere, the black powder was placed in a stainless steel ball mill jar and ball-milled to obtain Sm. 1.7 Mg 98.3 +10 wt.%TiO2(F) / M@C hydrogen storage alloy composite material.
3. The SmS ... 1.7 Mg 98.3 A method for preparing hydrogen storage alloy composite materials, characterized in that, In step S11, the volume ratio of tetrabutyl titanate to acetic acid and hydrofluoric acid is 15:(10-40):
5.
4. The SmS ... 1.7 Mg 98.3 A method for preparing hydrogen storage alloy composite materials, characterized in that, In step S12, the temperature during the hydrothermal treatment is 180-200 ℃, and the time is 10-15 h.
5. The SmS ... 1.7 Mg 98.3 A method for preparing hydrogen storage alloy composite materials, characterized in that, In step S21, the metal salt is Ni(NO3)2·6H2O or Co(NO3)2·6H2O.
6. The SmS ... 1.7 Mg 98.3 A method for preparing hydrogen storage alloy composite materials, characterized in that, In step S21, the molar ratio of TiOF2 to metal salt is 1:(2.5-5.5).
7. The SmS ... 1.7 Mg 98.3 A method for preparing hydrogen storage alloy composite materials, characterized in that, In step S22, during the heat treatment, the temperature is first increased from room temperature to 230°C at a heating rate of 5°C / min and held for 30 min, and then increased from 230°C to 500°C at a heating rate of 10°C / min and held for 2 h.
8. The SmS ... 1.7 Mg 98.3 A method for preparing hydrogen storage alloy composite materials, characterized in that, In step S31, the temperature during pre-hydrogenation is 425-550 ℃, the hydrogen pressure is 0.07-0.2 MPa, and the time is 1-4 h; during hydrogenation, hydrogenation is first performed once at 400 ℃ and 4.0 MPa for 12 h, followed by hydrogenation at 300 ℃ and 4.0 MPa for 12 h, and the hydrogenation step at 300 ℃ is repeated twice.
9. The SmS ... 1.7 Mg 98.3 A method for preparing hydrogen storage alloy composite materials, characterized in that, The ball milling process is as follows: ZrO2 and materials with a ball-to-material ratio of (35-60):1 are placed in a ball mill and milled at 400-550 rpm for 9-12 cycles. One cycle consists of 15-25 min of milling followed by 15-25 min of rest.